Pradakshina along the east of the adhisthana - Temples of India Project Team (Jio Institute, 2024)
Broken debris from the original temple assembled on the southeast face of the adhisthana. U-shaped rounded stones are assembled on the parapet, but their position or purpose in the original temple is unknown. The projected space attached to the adhisthana (centre) seems contemporary to the original temple and was likely used as a small shrine of the Panchayatan plan. The pradakshina along the east of the adhisthana has been paved with stone by the Archaeological Survey of India (ASI).